IMPLEMENTASI PERATURAN DAERAH PROVINSI KALIMANTAN TIMUR NOMOR 5 TAHUN 2015 TENTANG PENCEGAHAN PENYALAHGUNAAN INHALAN (STUDI KASUS DI KOTA SAMARINDA) - Gumay, Astrid Selfana (Jurnal Administrative Reform, 2020)
This article will review the achievements of implementing the East Kalimantan Provincial Regulation Number 5 of 2015 concerning Inhalant Abuse prevention. With a qualitative descriptive analysis research model with data collection techniques by observation, interviews, documentation, and interactive data analysis, the results showed that East Kalimantan Provincial Regulation Number 5 of 2015 concerning Inhalant Abuse Prevention Samarinda City has not been going well. There are various kinds of obstacles in the implementation process, such as the lack of human resources, lack of facilities and infrastructure, and people who comply with local regulations.Keywords: implementation, prevention, abuse, inhalation, local regulations